2006
DOI: 10.1111/j.1538-7836.2006.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of protein C inhibitor in monocrotaline‐induced pulmonary hypertension

Abstract: Summary. Background: Protein C inhibitor (PCI) plays a role in multiple biological processes including fertilization, coagulation, fibrinolysis and kinin systems. Objectives: We hypothesized that PCI participates in the pathogenesis of pulmonary hypertension. To demonstrate this, we compared the development of pulmonary hypertension in mice overexpressing PCI in the lung with wild-type (WT) mice. Pulmonary hypertension was induced by s.c. injection of 600 mg kg )1 of monocrotaline weekly for 8 weeks. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…In humans, the functional role in vivo was tested in venous thrombosis, where elevated levels of PCI constituted a mild risk factor for thrombosis (Meijers et al 2002) indicating that of the possible actions of PCI: anticoagulant by inhibition of coagulation enzymes, anti-antifibrinolytic by inhibition of the thrombin activatable fibrinolysis inhibitor (TAFI) activation by thrombin-thrombomodulin, anti-anticoagulant by inhibition of activated protein C and protein C activation by thrombomodulin, and antifibrinolytic by the inhibition of urokinase, the last two options predominate in vivo. In rodents, the functional role of PCI has been studied in vivo in genetically modified mice (Hayashi et al 2004; Nishii et al 2006; Uhrin et al 2000; Wagenaar et al 2000). Male homozygous PCI deficient mice are sterile due to severely impaired spermatogenesis probably caused by a disruption of the Sertoli cell barrier (Uhrin et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the functional role in vivo was tested in venous thrombosis, where elevated levels of PCI constituted a mild risk factor for thrombosis (Meijers et al 2002) indicating that of the possible actions of PCI: anticoagulant by inhibition of coagulation enzymes, anti-antifibrinolytic by inhibition of the thrombin activatable fibrinolysis inhibitor (TAFI) activation by thrombin-thrombomodulin, anti-anticoagulant by inhibition of activated protein C and protein C activation by thrombomodulin, and antifibrinolytic by the inhibition of urokinase, the last two options predominate in vivo. In rodents, the functional role of PCI has been studied in vivo in genetically modified mice (Hayashi et al 2004; Nishii et al 2006; Uhrin et al 2000; Wagenaar et al 2000). Male homozygous PCI deficient mice are sterile due to severely impaired spermatogenesis probably caused by a disruption of the Sertoli cell barrier (Uhrin et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Male homozygous PCI deficient mice are sterile due to severely impaired spermatogenesis probably caused by a disruption of the Sertoli cell barrier (Uhrin et al 2000). In transgenic mice overexpressing PCI in multiple organs, including the lung, the role of PCI in protection against monocrotaline-induced pulmonary hypertension was described (Nishii et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…BAL fluid levels of thrombin-antithrombin complex, monocyte chemoattractant protein-1, platelet-derived growth factor and IL-13, and the plasma level of TNFa were significantly increased in treated WT mice compared to hPCI Tg animals. 74 This study established that PCI in the lung is protective against monocrotaline-induce hypertension. Furthermore, it suggested that PCI fulfills both anti-inflammatory and anticoagulant activities in the lung.…”
Section: -22mentioning
confidence: 88%
“…This hPCI Tg animal system may be used as a tool to further explore PCI function in the lung under physiological and pathological conditions, as well as to test the therapeutic effect of human APC in vivo. Nishi et al 74 used the hPCI Tg mouse to identify a role for PCI in pulmonary hypertension. Monocrotaline treatment was used to specifically induce pulmonary hypertension.…”
Section: -22mentioning
confidence: 99%
See 1 more Smart Citation